IPad all-in-one for dummies - Muir, Nancy 1954- (John Wiley & Sons, Inc., 2015)
This guide provides step-by-step guidance for iPad and iPad mini users looking to make the most of this small wonder at home, at work, or on the go. Topics include: pick the iPad model that's right for you and discover cool bling you can add to.
"Covers iPad Air, iPad Air 2, iPad mini, iPad mini 2, & iPad mini 3"--Cover. - "5 books in 1"--Cover. - Print version record
Keywords: iPad (Computer); Tablet computers; iPad (Ordinateur); Tablettes électroniques